Characterization of the complete mitochondrial genome of the hybrid grouper Epinephelus akaara ♀ × Epinephelus tukula ♂, with its phylogenetic analysis. Issue 2 (3rd July 2019) - Li, Zhentong; Tian, Yongsheng; Li, Linlin; Wu, Yuping; Zhang, Jingjing; Li, Ziqi; Wang, Linna; Cheng, Meiling; Pang, Zunfang; Ma, Wenhui; Zhai, Jieming
Abstract: Epinephelus akaara ♀ × Epinephelus tukula ♂ is an economically important fish. The mitochondrial genome of the hybrid grouper had a double-stranded DNA molecule with the length of 16, 928 bp and consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a control region. The gene composition of the hybrid grouper mitochondrial genome was similar to that of most other vertebrates. Furthermore, phylogenetic analysis by maximum-likelihood (ML) method, based on the nucleotide sequences of 13 protein-coding genes, showed that the hybrid grouper has the closer relationship to Epinephelus akaara and confirmed that the mitochondrial genome is maternally inherited.